Pengaruh Servant Leadership Terhadap Komitmen Organisasi dan Organization Citizenship Behavior - Wike Santa Mira; Meily Margaretha (Jurnal Manajemen Maranatha, 2012)
This study was conducted to examine the influence of servant leadership toward organizational commitment and organizational citizenship behavior. Data distributed to 50 employees of Library Center of Maranatha Christian Universitywith 100% return rate with all the questionnaires used without disabilities. From the hypothesis analysis, it was found that servant leadership has a positive influence toward organization commitment and organization citizenship behavior. Themanagerial implications that can be applicated from those results, some others: the leader shows more concern of the team member; the leader accomodates any ideas/suggestions/aspirations of all employees and chooses an idea/suggestion/best aspiration; the leader more reapplies the vision, mission, objectives, programs, and regulatory organization; the leader with a humble heart and whole-heartedappreciates to the employees who has a high work performance.